10‐kHz High‐Frequency SCS Therapy: A Clinical Summary. Issue 5 (7th November 2014) - Russo, Marc; Van Buyten, Jean‐Pierre
Abstract Objective Chronic pain remains a serious public health problem worldwide. A spinal cord stimulation (SCS) therapy called HF10 SCS uses 10‐kHz high‐frequency stimulation to provide pain relief without paresthesia. In this article, we describe the therapy, device, and the methods of implant and then review the safety and effectiveness data for this therapy. Results HF10 SCS uses a charge‐balanced stimulation waveform that has been shown to be safe in both animal and human studies. Data from a multicenter, prospective clinical trial shows that the therapy provides substantial back and leg pain relief. Numerous additional reports suggest improved pain relief in other body areas and for complex pain patterns, even for patients who have previously failed other neuromodulation therapies. Conclusions The clinical experience reported in this article supports the efficacy and pain relief provided by HF10 SCS therapy. Clinical studies have also concluded that HF10 SCS does not generate paresthesia nor was it necessary to provide adequate coverage for pain relief. As clinical evidence accumulates and technological innovation improves patient outcomes, neuromodulatory techniques will be sought earlier in the treatment continuum to reduce the suffering for the many with otherwise intractable chronic pain.